Applying Andy English in Teaching Writing Skill - Forsia, Lastry; Nirmala, Nirna; Nuraini, Hery (International Education Trend Issues, 2023)
English essay writing is a skill that university students should develop. However, many students find it difficult to acquire that skill. Technology provides many advantages in teaching and learning process, not to mention to help students develop their writing skill. Andy English is one of application like instant messangers, but the users can do conversation or chatting with robot. The aim of this research was to know the effect of Andy English Application in improving students’ writing skill. This research was conducted for 2nd semester students of Economic Education at University of Islamic Syekh Yusuf. This study was quantitative research with a pre-experimental design one group pre-test and post-test. There were 12 students as a sample. The data collected by the pre test, treatment and post test. The data was analyzed by using t-test formula. The result shows that Asymp.sig (2 tailed) is less than α (0.000 < 0.05), it means that Ho is rejected and Ha is accepted. By calculating the data it can be concluded that there is a significant effect of applying Andy English apps in improving students’ writing skill. Andy English apps also can improve students’ vocabulary and develop self-confident in their writing skill. So it is recommended for the teacher to overcome any problems in learning English especially in writing.